Multidimensional background examination of young underweight Japanese women: focusing on their dieting experiences - Murofushi, Yuka; Yamaguchi, Shinji; Kadoya, Haruka; Otsuka, Hikaru; Ogura, Kasane; Kaga, Hideyoshi; Yoshizawa, Yasuyo; Tamura, Yoshifumi (Frontiers in Public Health, 2023)
Introduction This study examines the background of underweight young women in Japan from multiple perspectives, focusing on whether they have ever dieted. Methods A screening survey was administered to 5,905 underweight (BMI < 18.5 kg/m2) women aged 18–29 years, who could report their birth weight recorded in their mother-child handbook. Valid responses were obtained from 400 underweight and 189 normal-weight women. The survey collected data regarding height, weight (BMI), body image and perception of weight, dieting experience, exercise habits from elementary school age onwards, and current eating habits. Additionally, five standardized questionnaires were used (EAT-26, eHEALTH, SATAQ-3 JS, TIPI-J, and RSES). The primary analysis was a comparative analysis (t-test/χ2)—with the presence or absence of underweight and diet experience as independent variables, and each questionnaire as a dependent variable. Results The screening survey revealed that approximately 24% of the total population was underweight, with a low mean BMI. Of the respondents, more than half reported their body image as skinny and a small percentage as obese. Compared with the non-diet-experienced group (NDG), the diet-experienced group (DG) had a significantly higher proportion of past to current exercise habits. There was a significantly higher percentage of disagreement responses from the DG for weight and food gain than for the NDG. The NDG weighed significantly less than the DG in terms of birth weight, and lost weight easier than the DG. Additionally, the NDG was significantly more likely to agree with increasing weight and food intake. The NDG’s exercise habits were below 40% from elementary school age to the present, predominantly owing to a dislike for exercise and a lack of opportunity to implement it. In the standardized questionnaire, the DG was significantly higher for EAT-26, eHEALTH, SATAQ-3 JS, and Conscientiousness (TIPI-J), whereas the NDG was only significantly higher for Openness (TIPI-J). Discussion The results suggest the need for different health education programs for underweight women who desire to lose weight and experience dieting and for those who do not. This study’s results are reflected in the development of sports opportunities optimized for each individual, and in the development of measures to ensure adequate nutritional intake.